Implementasi Wireless Sensor Network Dengan Menggunakan Protokol OLSR pada Arduino Pro Mini dan NRF24L01 - Andreas Widyatmoko; Sabriansyah Rizqika Akbar; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Wireless Sensor Network is a wireless networking technology that connects multiple sensor nodes into a single network that work together to perform specific functions and objectives. In a network there is a set of rules that underlie the performance of the network itself, the rule is called protocol. OLSR is one of the proactive routing protocols. Unlike the LSR, the OLSR protocol applies the Multi Point Relay (MPR) mechanism to prevent duplicate message reception. In this research the implementation of OLSR protocol on Arduino Pro Mini and NRF24L01 is done to see how OLSR protocol performance in Arduino device and NRF24L01. The implementation will be divided based on the package message according to OLSR protocol. The results of this study indicate that the OLSR protocol can be implemented in Arduino Pro Mini and NRF24L01 devices. The results of this study indicate that the OLSR protocol can be implemented well on base station nodes and node sensing, which consists of Arduino Pro Mini and NRF24L01 devices. The packages used on the system are HELLO, MPR packets, mpr_info packets and sensor data packets. In addition, in the system there are several processes that update the routing table, forwarding and MPR node selection. Tests for HELLO packets, MPR packets and data sensor packets overall have a 100% success percentage. In addition, the authors also tested the convergence time of the protocol with an average value of 46002,9ms.